'Practical recognition' as a suitable pathway for researching just energy futures: Seeing like a 'modern' electricity user in Ghana. (February 2020) - Boamah, Festus; Rothfuß, Eberhard
Highlights: Energy justice scholarship reduces spatial and misrecognition injustices to spatial inequalities in energy access and unjust distribution. Universalizing energy access and a just distribution 'for all' are considered the remedy to these challenges. Such considerations downplay entitlement notions, the capacity to aspire and agency which are crucial determinants of context-specific energy demand patterns. Practical recognition provides a suitable pathway to study how energy initiatives practically address energy needs and visions of different groups. Abstract: Governmental and non-governmental actors promoting the universalisation of energy access and a just energy distribution for all envision spatial energy justice and recognition. Yet how and the extent to which these considerations offer practical solutions to the energy needs and visions of different social groups simultaneously is less evident. This is particularly crucial in Ghana where a just, 'state-driven' electricity provision connotes recognition of privileges of citizenship and an aura of 'modernity'. Many urban households in Ghana are keenly installing Solar Home Systems (SHS) to mitigate frequent grid power outages and ensure stability in the performance of social and energy-saving practices which grant them recognition as 'enlightened' social groups or as individuals staying au courant with modern energy technologies. Also, the Ghanaian government recently attempted to achieve spatial energy justice by providing free 500 W SHS to non-electrified, 'territorially remote' communities. Many community residents, however, claim the SHS facility restricts performances of 'modern' practices in comparison to fellow 'Ghanaians' who have access to electrical grids and that its acceptance may perpetually reduce them to 'second-class'/'old-fashioned citizens'. Our empirical evidence suggests that energy justice visions remain fuzzy unless they are set in relation to how and why practical solutions to the energy 'needs' and 'visions' of socially and spatially differentiated groups could be realised. We call this practical recognition . In this paper, we advocate practical recognition as a suitable alternative pathway for researching just energy futures by emphasizing connections between justice, human agency and entitlement notions.